Histopathological Changes and Metallothionein Levels in Filopaludina javanica During Depuration - Aminin Aminin; Diana Arfiati; Sri Andayani (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
The heavy metal lead has been reported to pollute waters along the Glagah River, Lamongan Regency, Indonesia. Lead contamination in all organs of the Tutut snail (Filopaludina javanica) was detected at 2.92 ± 0.5 ppm. Therefore, lead contamination can cause severe problems because lead can accidentally accumulate in the human body through the food chain. One effort to reduce risks related to food safety is Depuration. The research aimed to analyze the effect of Depuration using a flushing system on histopathological changes and metallothionein levels in all organs of the spotted snail (Filopaludina javanica). The research used a Completely Randomized Design with four treatments and three replications. Treatment includes flushing time (6 hours, 12 hours, 18 and 24 hours). The MT response was tested statistically using One Way Anova, while the histopathological analysis used a descriptive method by comparing before treatment and after flushing treatment for 24 hours, to determine metallothionein levels, the ELISA (Enzyme-Linked Immunosorbent Assay) method was used. The results showed tissue damage in edema, hyperplasia, and vacuolation. Tissue damage before and after Depuration was relatively the same and included in the low category, with damage ranging from (0-6.1%). Meanwhile, metallothionein analysis has not shown a significant decrease in levels. Metallothionein levels increased with the duration of flushing. Further checks showed that the media water used in flushing during Depuration contained Fe and Zn, which resulted in increased MT levels